THE ROLES OF ICT DEVELOPMENT IN OPEN AND DISTANCE EDUCATION: ACHEIVEMENTS, PROSPECTS AND CHALLENGES - Dickson Ogbonnaya Igwe (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2012)
The promises of information and communication technologies (ICT) have driven e-learning in transforming open distance education and thereby advancing the knowledge economy that rested on three arguments: E-learning could expand and widen access to tertiary education and learning; improve the quality of education; and reduce its cost. This article evaluates these three promises based on existing data and evidence. It concludes that the reality has not matched the promises so far in terms of pedagogic innovation. This does not mean that ICT development has not produced any significant positive results in improving the overall learning (and teaching) experience in the institutions and societies where it is implemented. That implies that what will help further to identify the new challenge. ICT development faces will be further research. Obstacles and problems of ICT that could have affected the open educational resource initiatives are yet to be established. The first section of the paper recalls some of the proposed values of e-learning. The second section compares achievements so far and suggests that e-learning could be only at an early stage of realising educational innovation aspirations. The third section highlights the challenges of future developments in e-learning.